Small Extracellular Vesicles Propagate the Inflammatory Response After Trauma. - Seibold, Tanja; Schoenfelder, Jonathan; Weeber, Florian; Lechel, Andre; Armacki, Milena; Waldenmaier, Mareike; Wille, Christoph; Palmer, Annette; Halbgebauer, Rebecca; Karasu, Ebru; Huber-Lang, Markus; Kalbitz, Miriam; et al. (Advanced Science, 2021)
Trauma is the leading cause of death in individuals under 44 years of age. Thorax trauma (TxT) is strongly associated with trauma-related death, an unbalanced innate immune response, sepsis, acute respiratory distress syndrome, and multiple organ dysfunction. It is shown that different in vivo traumata, such as TxT or an in vitro polytrauma cytokine cocktail trigger secretion of small extracellular nanovesicles (sEVs) from endothelial cells with pro-inflammatory cargo. These sEVs transfer transcripts for ICAM-1, VCAM-1, E-selectin, and cytokines to systemically activate the endothelium, facilitate neutrophil-endothelium interactions, and destabilize barrier integrity. Inhibition of sEV-release after TxT in mice ameliorates local as well as systemic inflammation, neutrophil infiltration, and distant organ damage in kidneys (acute kidney injury, AKI). Vice versa, injection of TxT-plasma-sEVs into healthy animals is sufficient to trigger pulmonary and systemic inflammation as well as AKI. Accordingly, increased sEV concentrations and transfer of similar cargos are observed in polytrauma patients, suggesting a fundamental pathophysiological mechanism.
EVALuna2:493174